2015
DOI: 10.1074/jbc.m114.625137
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Modulation of Cellular SNAT2 (SLC38A2) Abundance and Function by Unsaturated Fatty Acid Availability

Abstract: Background: Cellular amino acid withdrawal/hypertonicity induces an adaptive increase in the expression, stability, and function of the SNAT2 amino acid transporter.Results: Linoleic acid, a polyunsaturated fatty acid, suppresses the adaptive increase by targeting SNAT2 for proteolysis.Conclusion: Linoleic acid promotes SNAT2 degradation via the ubiquitin/proteasome pathway.Significance: The study provides the first evidence that SNAT2 stability is modulated by fatty acid availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…A recent study has suggested that proteasomal degradation explains decreased SNAT2 induction by unsaturated fatty acids under stress conditions (31). Inhibition of the proteasome caused the accumulation of immature SNAT2 but not the fully glycosylated transporter (31). In our experiments, decreased SNAT2 protein caused by Sal was not due to proteasomal degradation.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…A recent study has suggested that proteasomal degradation explains decreased SNAT2 induction by unsaturated fatty acids under stress conditions (31). Inhibition of the proteasome caused the accumulation of immature SNAT2 but not the fully glycosylated transporter (31). In our experiments, decreased SNAT2 protein caused by Sal was not due to proteasomal degradation.…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported that turnover of the SNAT2 protein depends on the ubiquitin proteasome system via the involvement of the ubiquitin E3 ligase NEDD4-2 (44). A recent study has suggested that proteasomal degradation explains decreased SNAT2 induction by unsaturated fatty acids under stress conditions (31). Inhibition of the proteasome caused the accumulation of immature SNAT2 but not the fully glycosylated transporter (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, another amino acid transporter, system A/SNAT2 (SLC38A2), is regulated differentially at the transcriptional and post-translational levels. Amino acid starvation and hypertonicity increase SNAT2 mRNA; however, stress conditions promote the proteasome-dependent degradation of SNAT2 39, 40 . It is possible that LAT1 in beta cells could be differentially regulated at the transcriptional and post-translational level in a similar manner, with nutrient availability and/or signaling determining the trafficking or degradation of LAT1 protein.…”
Section: Discussionmentioning
confidence: 99%